ANALISIS EKONOMI RUMAH TANGGA PETANI JAGUNG DI DESA TOLOTIO KECAMATAN TIBAWA KABUPATEN GORONTALO - Elsy Febriani Datau; Yanti Saleh; Amelia Murtisari (Universitas Negeri Gorontalo, 2017)
This reseacrh aims at analyzing: 1) the sources of corn growers’ income in Tolotio Village Tibawa Sub district Gorontalo District, 2) houshold income of corn grower in Tolotio Village Tibawa Sub district Gorontalo District, and 3) household comsumption of corn grower in Tolotio Village Tibawa Sub district Gorontalo District. This research is conducted in Tolotio Village Tibawa sub district Gorontalo district staring from April to May 2017 with 50 corn growers as the samples. The method applies survey method. Data analysis applies descriptive analysis, farm income analysis, and household incoe analysis. Finding show that sources of corn growers’ income in Tolotio Village Tibawa Sub district Gorontalo District come from two sources which are the agriculture sectorand outer agricuture sector encompassing to artisan, driver, tradesman, and civil servant. The household income of corn grower in Tolotio Village Tibawa Sub district Gorontalo District is IDR. 5.881.173,92. Based on the farm income is IDR. 1.140.000. the household consumption is clustered into food and non-food consumtions. The average of household consumtion in Tolotio Village Tibawa Sub district Gorontalo District is IDR. 5.832.940/season.